2014
DOI: 10.1088/0004-637x/787/2/100
|View full text |Cite
|
Sign up to set email alerts
|

On the Helicity of Open Magnetic Fields

Abstract: We reconsider the topological interpretation of magnetic helicity for magnetic fields in open domains, and relate this to the relative helicity. Specifically, our domains stretch between two parallel planes, and each of these ends may be magnetically open. It is demonstrated that, while the magnetic helicity is gaugedependent, its value in any gauge may be physically interpreted as the average winding number among all pairs of field lines with respect to some orthonormal frame field. In fact, the choice of gau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 27 publications
0
103
0
Order By: Relevance
“…For relative magnetic helicity to be gauge invariant, the reference field must have the same distribution of the normal component of the studied field B along the surface. A classical choice, adopted here, is to use the potential field B p as the reference field (see Prior & Yeates 2014, for a possible different class of reference field). As in Valori et al (2012), we use here the definition of relative magnetic helicity from Finn & Antonsen (1985):…”
Section: Relative Magnetic Helicity Measurementsmentioning
confidence: 99%
“…For relative magnetic helicity to be gauge invariant, the reference field must have the same distribution of the normal component of the studied field B along the surface. A classical choice, adopted here, is to use the potential field B p as the reference field (see Prior & Yeates 2014, for a possible different class of reference field). As in Valori et al (2012), we use here the definition of relative magnetic helicity from Finn & Antonsen (1985):…”
Section: Relative Magnetic Helicity Measurementsmentioning
confidence: 99%
“…It is therefore desirable to restrict oneself to gauges that measure winding with respect to a fixed basis, which makes A gauge invariant for a given frame. Furthermore, it has been shown that the choice of basis used to measure winding of field lines corresponds directly to a choice of reference field for relative helicity, 7 so there is an equivalence between the relative helicity and winding interpretations.…”
Section: B Field Line Helicitymentioning
confidence: 99%
“…(9), hence the U terms cancel for every field line. Physically, this restriction ensures that A measures winding with respect to a time-independent frame, eliminating nonphysical changes, 7 or equivalently that A is a field line helicity for relative helicity with a time-independent reference field. 31 The W terms correspond to a net voltage drop along the field line.…”
Section: B Interpretation Of Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, magnetic helicity does have a local density per elementary flux tube, namely, the field line helicity defined as the integral of A along a magnetic field line (Yeates & Hornig 2014Russell et al 2015). Besides the relative magnetic helicity in Equation (1), there are some other expressions and interpretations of the magnetic helicity (Jensen & Chu 1984;Hornig 2006;Low 2006Low , 2011Longcope & Malanushenko 2008;Prior & Yeates 2014). Here, we only focus on the relative magnetic helicity.…”
Section: Introductionmentioning
confidence: 99%